2021
DOI: 10.1038/s41598-021-88734-2
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic delay of associated interstitial lung disease increases mortality in rheumatoid arthritis

Abstract: Rheumatoid arthritis (RA) is a systemic autoimmune disease whose main extra-articular organ affected is the lung, sometimes in the form of diffuse interstitial lung disease (ILD) and conditions the prognosis. A multicenter, observational, descriptive and cross-sectional study of consecutive patients diagnosed with RA-ILD. Demographic, analytical, respiratory functional and evolution characteristics were analyzed to evaluate the predictors of progression and mortality. 106 patients were included. The multivaria… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 46 publications
1
13
0
1
Order By: Relevance
“… 41 43 Delay in referral to speciality centres has been associated with increased mortality in interstitial lung disease. 44 , 45 Our findings are corroborated by the results of a European survey of patients with idiopathic pulmonary fibrosis who also described a protracted route to obtaining a diagnosis. 46 In this survey, patients viewed their initial diagnosis of asthma, COPD or pneumonia, not as a working hypothesis, but as an error or misdiagnosis.…”
Section: What Is Already Knownsupporting
confidence: 80%
“… 41 43 Delay in referral to speciality centres has been associated with increased mortality in interstitial lung disease. 44 , 45 Our findings are corroborated by the results of a European survey of patients with idiopathic pulmonary fibrosis who also described a protracted route to obtaining a diagnosis. 46 In this survey, patients viewed their initial diagnosis of asthma, COPD or pneumonia, not as a working hypothesis, but as an error or misdiagnosis.…”
Section: What Is Already Knownsupporting
confidence: 80%
“…As our cohort showed generally better baseline pulmonary function than those of previous studies, 32 we may assume that this study cohort includes more patients who diagnosed ILD in early stage. Recent study suggests that delayed diagnosis of RA-ILD associated with an increased mortality, 33 and, thus, diagnosing RA-ILD in early stage might have resulted in lower mortality in our cohort.…”
Section: Discussionmentioning
confidence: 70%
“…Current research in non-ARD ILDs has shown that significant diagnostic delay is often caused by factors such as misdiagnosis, underreporting of ILD features on imaging and prolonged referral time to ILD specialists, even when ILD is reported [ 14–17 ]. Similarly, previous studies on ARD-ILD have found that the time from symptom debut to diagnosis is delayed and that diagnostic delay is associated with disease progression and increased mortality [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 71%